Pengaruh Model Pembelajaran Kooperatif Tipe Think Talk Write Terhadap Pemahaman Konsep Pada Pembelajaran IPAS - Nabila, Nabila Safitri; Khoiri, Ahmad; Sulilawati, Indria Sulilawati; Fitriana, Iin Mahlia (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to determine the effect of the Think Talk Write (TTW) cooperative learning model on students’ conceptual understanding in IPAS learning for Grade IV at SDN 01 Nanga Kelawai. The research used a quantitative method with a pre-experimental one-group pretest-posttest design. The sample consisted of 17 students selected through a saturated sampling technique. The instrument was a validated and reliable Two-Tier multiple-choice test, and data were analyzed using the Wilcoxon test. Results showed that the average pretest score was 41.35, while the posttest score increased to 56.35, with a gain of 15.70 points. The Wilcoxon test produced a Z value of 3.623 and an Asymp. Sig. (2-tailed) of 0.001 < 0.05, indicating that Ha was accepted and Ho rejected. Therefore, the Think Talk Write (TTW) model significantly affects students’ conceptual understanding.